2006
DOI: 10.1002/ijc.22231
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic acid modulates histone acetylation and induces differentiation and senescence

Abstract: Agents that can modulate colonic environment and control dysregulated signaling are being evaluated for their chemopreventive potential in colon cancer. Ursodeoxycholate (UDCA) has shown chemopreventive potential in preclinical and animal models of colon cancer, but the mechanism behind it remains unknown. Here biological effects of UDCA were examined to understand mechanism behind its chemoprevention in colon cancer. Our data suggests that UDCA can suppress growth in a wide variety of cancer cell lines and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 68 publications
1
33
0
1
Order By: Relevance
“…Here, we showed that DCA in weakly acidic conditions affected the barrier function, indicating that, even if acid suppression is successful, weakly acidic reflux with DCA can damage the esophagus. While bile acids, including GCA, TCA, and DCA, are known to damage barrier function (22,30) or to affect colon tumor promoters (20), UDCA is thought to be chemopreventive (1). Although the solubility of UDCA was low in the culture media, we examined the influence of UDCA at maximum concentration at pH 3, and it did not affect the barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that DCA in weakly acidic conditions affected the barrier function, indicating that, even if acid suppression is successful, weakly acidic reflux with DCA can damage the esophagus. While bile acids, including GCA, TCA, and DCA, are known to damage barrier function (22,30) or to affect colon tumor promoters (20), UDCA is thought to be chemopreventive (1). Although the solubility of UDCA was low in the culture media, we examined the influence of UDCA at maximum concentration at pH 3, and it did not affect the barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…,112 Recent mechanistic studies suggest that, in contrast to butyrate, UDCA induced cell differentiation and senescence in colon cancer cells via histone hypoacetylation. 113 …”
Section: Ursodeoxycholate (Udca)mentioning
confidence: 99%
“…It is currently known that p300, together with its closely related factor CBP, is present in most cell types (46), where it may interact with a large number of DNA-bound nuclear receptors and nuclear factors to form a large acetyltransferase complex - a useful database for the CBP/p300 interactome is currently available ("CBP & p300 interactome database"; found at http://www.stjude.org/brindle) - and participate in second messenger-regulated gene expression (47)(48)(49)(50). Curiously, high doses of UDCA (500 ÎŒM) have recently been reported to diminish histone acetylation in several cell lines from colon cancer (51), but this effect appears unrelated to what we have observed in our study, and a direct effect of UDCA on the CBP/p300 complex and interacting nuclear proteins remains to be elucidated. Although the detailed mechanism of action of p300 for AE2 alternate promoter deserves deeper studies, our present data from ChIP assays against p300 in nuclear extracts from nontransfected PLC/PRF/5 cells suggest that this coregulator may interact with DNA-bound HNF1α on the AE2 alternate promoter regardless of any treatment ( Figure 12, B and C).…”
Section: Figure 10mentioning
confidence: 99%